Development and Effectiveness of Interactive Wordwall Digital Media for Early Childhood Literacy - Taopik Rahman; Sadick Akida Mwariko; Nisna Nursarofah; Anggi Maulana Rizqi; Thiana Nurussakinah (FKIP Universitas Lampung, 2026)
This study aimed to develop interactive Wordwall-based digital media for children aged 4-5 years and evaluate its feasibility, practicality, and effectiveness in improving early literacy skills, particularly letter recognition and phonemic awareness. This R&D study applied the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and was conducted at TK Cerdik and TK Sejahtera 4 in West Java, Indonesia. Participants included teachers and children aged 4-5 years. Feasibility was assessed through expert validation (material, media, and pedagogical experts). Practicality was tested in a small-group trial (n=10), and effectiveness was measured through pre- and post-test literacy assessments in a large-group trial (n=30), with results analyzed using the normalized gain (N-gain) formula. Needs analysis showed that 90% of children were at the “beginning to develop” literacy stage, reflected in a pre-test average of 4.4 (low). Expert validation scores were 80% for material (feasible), 80% for media (feasible), and 100% for pedagogy (very feasible), placing the overall product in the very feasible category. The pedagogical score was based on a structured six-component rubric covering curriculum alignment, developmental appropriateness, play-based learning principles, and teacher usability. The small-group trial yielded a practicality rating of 100% (very feasible). In the large-group trial, the post-test average increased to 10.4, yielding an N-gain of 0.8 (high effectiveness). The most notable improvements were in letter recognition and letter-sound matching. Wordwall-based interactive digital media is feasible, practical, and highly effective in enhancing early childhood literacy among children aged 4-5 years. The media offers an evidence-based, culturally responsive alternative to conventional instructional tools and can be integrated into daily early childhood education practice. Keywords: early childhood literacy, interactive media, wordwall, digital learning, media development.